The changing legal environment of the juvenile court - Mays, George Larry (American journal of criminal justice, 1979)
The American juvenile court is in a state of legal flux. From its informal beginning in English chancery law, to its formal inception in the United States in 1899, the court has been exposed to a number of diverse, competing pressures. Since the Supreme Court case of In re Gault in the mid-1960’s, the whole underpinnings of the juvenile court have been so shaken that one must now ask whether or not the last vestiges of parens patriae have been swept away. If this is indeed the case, America should now seek alternatives to the present system of juvenile adjudication —for the sake of the child and for the sake of justice.